Winter Exponential Smoothing: Sales Forecasting on Purnama Jati Souvenirs Center - Fahrobby Adnan; Putri Damayanti; Gama Fajarianto; Antonius Cahya Prihandoko (IAES Indonesia Section, 2018)
Forecasting is the process of making predictions of the future based on past and present data and most commonly by analysis of trends. In sales area, an accurate sales forecasting system will help the company to improve the customers' satisfaction, reduce destruction of products, increase sales revenue and make production plan efficiently. Purnama Jati is a typical Jember souvenir place like